Can openness be planned? An essay on the temporal dimension in spatial planning - Yvonne Siegmund (Spatial transformation: Processes, strategies, research design, 2022)
Urban planning processes manoeuvre within the interplay between constantly shifting global, regional and local dynamics. Considering processes from a temporal perspective can therefore provide a key to understanding these complex contexts. Although the time factor is still largely ignored in planning practice, some exceptions, such as rapid planning or slow urbanism, experiment with it. In these cases, planning processes are either accelerated and simplified or expanded and designed openly. This essay focuses on the slow, open-process developments of creative quarters in Munich and Hamburg. In both cases, the temporal dimension will be used to elucidate path dependencies in the negotiation and design of urban spaces.
urn:nbn:de:0156-08911369; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Time; temporalities; planning time; space-time; slow urbanism; fast urbanism; open planning; creative quarter; acceleration; deceleration; own times; timescapes; time structures; openness; flexibility